(untitled) (Journal of Applied Business and Economics, 2024)
We examined the impact of the COVID-19 on a Southern California public university’s the Business Assessment Test (BAT) scores. The analysis analyzed over 4,000 observations from Spring 2017 to Spring 2022. Results demonstrated a significant performance improvement during COVID, with the average BAT score increasing from 51.35 to 55.47. Furthermore, demographic factors like major, ethnicity, enrollment, gender, and English proficiency also influenced BAT scores. Finally, interaction effects, especially for quantitative test questions were significant between COVID and cs major, work, and language. The study provides insights for educators and policymakers regarding the implementation of online assessment format in the future.